THE ROLE OF CORPORATE GOVERNANCE IN PREVENTING FINANCIAL CRISES - Arunkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate governance plays a critical role in ensuring the stability, transparency, and accountability of financial institutions, thereby acting as a preventive mechanism against financial crises. Effective corporate governance frameworks help to mitigate risks, reduce instances of corporate misconduct, and ensure that businesses operate in a sustainable manner. Financial crises, often characterized by excessive risk-taking, poor decision-making, and lack of oversight, have historically been exacerbated by weak governance structures in financial institutions. This paper explores the key components of corporate governance such as board composition, executive compensation, risk management practices, and shareholder rights and how they contribute to preventing financial crises. By examining past financial crises and their roots in governance failures, the study highlights the importance of robust governance structures in promoting financial stability. Furthermore, the paper discusses regulatory reforms and best practices that can strengthen corporate governance and mitigate systemic risks in the financial system. Ultimately, this research emphasizes the need for improved governance practices to foster long-term economic stability and reduce the likelihood of future financial disruptions.